Environmental triggers of faunal changes revealed by benthic foraminiferal monitoring - Schoenfeld, Joachim (2021)
Benthic foraminifera are deemed sensitive indicators of environmental conditions. Triggers and magnitudes of faunal response to environmental changes are yet poorly constrained. Benthic foraminiferal faunas were monitored annually at Ria Formosa (Algarve, Portugal) coastal lagoon since 2013. Distinct environmental changes were recognised during the monitoring period. The relocation of a tidal inlet in winter 2015 effected faster flushing, higher tidal levels, and stronger currents in the Esteiro do Ancao tidal channel. The epibenthic foraminiferal species Asterigerinata mamilla increased in abundance and the population densities of the whole fauna were double as high as before inlet relocation. Enhanced sediment redeposition was recorded and extensive polychaete colonies successively replaced firmground patches with oysters. The standing stock of the foraminiferal fauna declined in the next year due to food impoverishment, while the high hydraulic energy levels and high percentages of Asterigerinata mamilla maintained. Benthic foraminifera responded much faster to environmental perturbations than macroorganisms identifying them as powerful proxies in environmental studies.